Pengaruh Kepemimpinan Transformasional Kepala Sekolah dan Budaya Sekolah Terhadap Kinerja Guru pada Sekolah Pengerak SMA di Kecamatan Sirimau Kota Ambon - Roodmansye E.I Salenussa; R. Kempa; J.E Lekatompessy; Sumarni Rumfot (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
The school mover program focuses on holistically developing student learning outcomes, including competency (literacy and numeracy) and character, starting with the formation of superior human resources (school principals and teachers). Running this program requires the effectiveness of a leader who can inspire, transferring the vision of educational institutions through school programs and school culture so that they can impact the quality of education in school mover. This research aims to 1) describe the transformational leadership of school principals who are senior high school movers in Sirimau District, Ambon City. 2) Describe the implementation of school culture for senior high school movers in Sirimau District, Ambon City. 3) Describe teachers' performance as senior high school movers in Sirimau District, Ambon City. 4) test the significance level and direction of the influence of the principal’s transformational leadership on teachers' performance at the senior high school mover in Sirimau District, Ambon City.5) test the significance level and direction of the influence of the school culture's influence on teachers' performance at the senior high school mover in Sirimau District, Ambon City. 6) test the level of significance of the influence of the principal’s transformational leadership and school culture on teachers' performance at senior high school mover in Sirimau District, Ambon City. This research used an associative method with a quantitative approach. The data collection tool was a questionnaire distributed to school principals and all teachers at the senior high school mover in Sirimau District, Ambon City. The population in this study was 200 people, and using random sampling techniques. A research sample of 133 people was obtained. The data analysis techniques were descriptive and inferential statistics (simple linear regression test and multiple linear regression). The research results of the descriptive analysis showed that the principal's transformational leadership, school culture and teachers performance at the senior high school mover in Sirimau District, Ambon City, are in the high category. Meanwhile, based on the results of hypothesis testing, it showed that there is a significant and positive influence between the principal's transformational leadership on teachers performance (21.1%), there is a significant and positive influence between school culture on teachers' performance (30.2%), and there is a significant and positive influence between the principal's transformational leadership and school culture together on teachers performance (32.9%).